GENDER-BASED DIFFERENCES IN MASTERING ENGLISH LANGUAGE SKILLS - Nurlindawati Nurlindawati; Burhanuddin Yasin; Abdul Hadi (Jurnal Ilmiah Didaktika, 2022)
This study aims to find out gender-based differences in mastering English language skills between male and female students in single-sex schooling. There were 330 participants from first and second-year students of Darul Ihsan Islamic Senior High School involved. Direct learning strategies (memory, cognitive, and compensation strategy) along with attitude, motivation, and anxiety are variables analyzed in this study. A questionnaire from the Strategy Inventory for Language Learning (SILL) and Attitude Motivation Test Battery (AMTB) were adapted to collect the data. The data were analyzed by using Mann Whitney-U Test. The findings from the partial test show there was a significant difference between male and female students in attitude, motivation, anxiety, memory strategy, and cognitive strategy. Only compensation strategy and the simultaneous test of the variables were found to have no statistically significant difference between male and female students. The finding of the English subject score showed that female students outperform male students. It also found that male students have a higher level of anxiety than female students. Therefore, it is suggested that teachers should try to adjust the teaching and learning in male classes so that hopefully the learning circumstance will reduce the anxiety of male students.